2022
DOI: 10.1111/papt.12393
|View full text |Cite
|
Sign up to set email alerts
|

The service user experience of SlowMo therapy: A co‐produced thematic analysis of service users’ subjective experience

Abstract: Objectives SlowMo is the first blended digital therapy for paranoia, showing significant small‐moderate reductions in paranoia in a recent large‐scale randomized controlled trial (RCT). This study explored the subjective service‐user experience of the SlowMo therapy content and design; the experience of the blended therapy approach, including the triangle of the therapeutic alliance; and the experience of the digital aspects of the intervention. Design Qualitative co‐produced sub‐study of an RCT. Methods Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 71 publications
0
19
0
Order By: Relevance
“…This was the first digitally supported therapy for paranoia to demonstrate efficacy (improved effect size compared to conventional CBTp was achieved in half of the minimum number of recommended sessions [ 65 ]), and the mechanism of change. A process evaluation of therapy experience demonstrated high rates of therapy uptake and adherence [ 66 ], a coproduced qualitative interview study supported the user experience and mechanism of change [ 67 ], and a user experience study showed that SlowMo bridged the “digital divide” as poorer digital literacy in Black people and older people did not translate to the user experience of SlowMo [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…This was the first digitally supported therapy for paranoia to demonstrate efficacy (improved effect size compared to conventional CBTp was achieved in half of the minimum number of recommended sessions [ 65 ]), and the mechanism of change. A process evaluation of therapy experience demonstrated high rates of therapy uptake and adherence [ 66 ], a coproduced qualitative interview study supported the user experience and mechanism of change [ 67 ], and a user experience study showed that SlowMo bridged the “digital divide” as poorer digital literacy in Black people and older people did not translate to the user experience of SlowMo [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen out of the nineteen studies were rated as high quality, with a score of 9 or above [12,[33][34][35][36][37][38][39][40][41][42][43][44][45][46]. The rest of the studies were rated as moderate quality, scoring either 7 or 8 [14,[47][48][49].…”
Section: Assessment Of Study Qualitymentioning
confidence: 99%
“…The item that was scored most poorly across the included studies was in relation to reflexivity and bias. Only seven out of the nineteen studies had a clear reflexivity statement or explanation of the researchers' relationship with the participants [12,33,34,39,42,44,45].…”
Section: Assessment Of Study Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…27 Participants' expectations were mainly related to increasing their health literacy, sense of belonging and the positive impact on the research, which have been previously described in other PPI initiatives. 28,29 Nevertheless, we need to consider that these expectations are voiced by participants without previous experience as research partners. Thus, it is advisable to have an ongoing assessment of expectations as network members gain research experience.…”
Section: Topic 1: Willingness To Participate In a Ppi Initiativementioning
confidence: 99%